Opposing Age-Related Trends in Absolute and Relative Risk of Adverse Health Outcomes Associated With Out-of-Office Blood Pressure - Li, Yan; Thijs, Lutgarde; Zhang, Zhen-Yu; Asayama, Kei; Hansen, Tine W; Boggia, José; Björklund-Bodegård, Kristina; Yang, Wen-Yi; Niiranen, Teemu J; Ntineri, Angeliki; Wei, Fang-Fei; Kikuya, Masahiro; et al. (Hypertension (Dallas, Tex., 2019)
Participant-level meta-analyses assessed the age-specific relevance of office blood pressure to cardiovascular complications, but this information is lacking for out-of-office blood pressure. At baseline, daytime ambulatory (n=12 624) or home (n=5297) blood pressure were measured in 17 921 participants (51.3% women; mean age, 54.2 years) from 17 population cohorts. Subsequently, mortality and cardiovascular events were recorded. Using multivariable Cox regression, floating absolute risk was computed across 4 age bands (≤60, 61-70, 71-80, and >80 years). Over 236 491 person-years, 3855 people died and 2942 cardiovascular events occurred. From levels as low as 110/65 mm Hg, risk log-linearly increased with higher out-of-office systolic/diastolic blood pressure. From the youngest to the oldest age group, rates expressed per 1000 person-years increased (P<0.001) from 4.4 (95% CI, 4.0-4.7) to 86.3 (76.1-96.5) for all-cause mortality and from 4.1 (3.9-4.6) to 59.8 (51.0-68.7) for cardiovascular events, whereas hazard ratios per 20-mm Hg increment in systolic out-of-office blood pressure decreased (P≤0.0033) from 1.42 (1.19-1.69) to 1.09 (1.05-1.12) and from 1.70 (1.51-1.92) to 1.12 (1.07-1.17), respectively. These age-related trends were similar for out-of-office diastolic pressure and were generally consistent in both sexes and across ethnicities. In conclusion, adverse outcomes were directly associated with out-of-office blood pressure in adults. At young age, the absolute risk associated with out-of-office blood pressure was low, but relative risk high, whereas with advancing age relative risk decreased and absolute risk increased. These observations highlight the need of a lifecourse approach for the management of hypertension.
Keywords: Health Status; Risk Assessment; lidé; self-management; sexuální faktory; Middle Aged; blood pressure monitoring; hypertenze; ambulantní monitorování krevního tlaku; kardiovaskulární nemoci; Sex Factors; Female; cardiovascular diseases; zdravotní stav; Internationality; Blood Pressure Monitoring, Ambulatory; věkové faktory; hodnocení rizik; Multivariate Analysis; multivariační analýza; internacionalita; Humans; návštěvy v ordinaci; ambulatory; Blood Pressure Determination; lidé středního věku; měření krevního tlaku; kohortové studie; Cohort Studies; mužské pohlaví; Cardiovascular Diseases; Hypertension; Office Visits; ženské pohlaví; Age Factors; Proportional Hazards Models; hypertension; Self-Management; proporcionální rizikové modely; Male; Aged; blood pressure; mortality; senioři